Safety Pharmacology Study of ET-26 Hydrochloride, a Potential Drug for Intravenous General Anesthesia, in Rats and Beagle Dogs - Zhang, YuJun; Jiang, YingYing; Chang, Pan; Kang, Yi; Gong, DeYing; Liu, Jin; Zhang, WenSheng (Frontiers in Pharmacology, 2021)
Background: ET-26 hydrochloride (ET-26HCl), a class 1 new drug, was developed to reserve the advantages of etomidate with a mild adrenocortical inhibition. Purpose: this study was to evaluate the potential adverse effects on the respiratory, cardiovascular, and central nervous systems. Methods: three established methods, the whole-body plethysmography for respiratory function, the prototype telemetry transmitter for cardiovascular function, and the standardized functional observational battery for central nervous system function, were accomplished with Good Laboratory Practice standards. Results: no significant difference in the tidal volume, but the respiratory rate and minute ventilation were reduced. The degree of inhibition was the most serious in the first 15 min after dosing and function fully recovered after 1 hour. Then, all the variations in cardiovascular functions were within the expected range for normal biological variation, we concluded that ET-26HCl, even at 5-fold 2ED50, still does not exert toxicological effects on the cardiovascular system. In functional observational battery tests, all the observed changes, including motor activity, behavior, coordination, and sensory and motor reflex responses, and reduced body temperature, were resulted in general anesthesia effect. Conclusion: ET-26HCl exerts mild, reversible effects on respiratory, cardiovascular, and central nervous system function as verified by standard in vivo animal models.